The Effect of Eight Weeks Training in Shallow Water on Static Balance of Military with Knee Injuries - Amin Roshandel Hesari; Ali Aoshandel Hesari; Ali Mohagheghi Pirshahid (Islamic Azad University, Hamedan Branch, 2021)
Objective The purpose of study was the effect of 8 weeks training shallow water on static balance of military with knee injuries. Methods Subjects of this research there were the Number of person 46 military in north khorasan province, They participated in this study purposefully and voluntarily. Subjects were randomly divided into two experimental groups of 23 people (Mean±SD, age (y) 33.65±6.62, height (cm) 183±6.95, weight (kg) 76.75±2.80) and a control group of 23 people (Mean±SD, age (y) 34.45±6.97, height (cm) 181±7.41, weight (kg) 71.66±3.20). To measure static balance were used the stork test. Were used For analyze the results of descriptive statistics (Mean±SD) and were used Inferential statistics method (Shapiro-Wilk test, dependent t and independent t). Results The test results showed there is a significant difference between pre-test and post-test in the experimental group (P=0.001). So that was not observed significant difference between pre-test and post-test in balance (P=0.393), Also, a significant difference was found between the experimental and control groups (P=‌0.001). Conclusion Based on research results, it can be concluded that shallow water training is significant on the static balance of soldiers with knee injuries and this can indicate the greater effectiveness of exercises in shallow water so practice in the water it can be recommended as a way to improve static balance in people with knee injuries.